On the study of a rational expectation model with lagged endogenous variables. Issue 3 (4th March 2019) - Hu, Chunhua; Lai, Shaoyong; Dou, Zheng
ABSTRACT: A rational expectation model with lagged endogenous variables is used to describe how the current price level is influenced by the expectation and historic price level. The time domain of the rational expectation model is extended to a complex discrete time domain which is a collection of points along the real number line. The rational expectation model with lagged endogenous variables is solved in multi-dimensional cases where the agents possess multiple assets, and the current price of each asset is related to the expected price and historical prices. An example about price determination process of storable commodities is given to illustrate the advantages of the rational expectation model on isolate time domain.